2021
DOI: 10.7235/hort.20210056
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Polyploidy in Cucumis melo ‘Chammel’ and Evaluation of Morphological and Cytogenetic Changes

Abstract: This study explored the effects of oryzalin on the polyploidization of a new cultivar, Cucumis melo 'Chammel'. 58 diploid seedlings of 'Chammel' were treated with oryzalin. Their ploidy levels were checked by flow cytometry and number of 5S and 18S rDNA loci were examined by fluorescence in situ hybridization (FISH). Twelve among 58 plants were identified as tetraploids. The tetraploids were self-crossed, and their seeds were harvested. The seeds and seedlings of the tetraploids were compared to the correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The phenomenon of gigantism caused by polyploidization has been frequently reported in plants from Cucurbitaceae and other families. For instance, in C. lanatus [22,23] and C. melo [18], induced tetraploid plants exhibited significantly larger flowers, leaves, seeds, and fruit size than diploid plants. However, a study by Bae et al [17] was not in line with these findings for tetraploid plants of C. lanatus, and the induced tetraploid plants showed small, thick, and crumpled leaves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenon of gigantism caused by polyploidization has been frequently reported in plants from Cucurbitaceae and other families. For instance, in C. lanatus [22,23] and C. melo [18], induced tetraploid plants exhibited significantly larger flowers, leaves, seeds, and fruit size than diploid plants. However, a study by Bae et al [17] was not in line with these findings for tetraploid plants of C. lanatus, and the induced tetraploid plants showed small, thick, and crumpled leaves.…”
Section: Discussionmentioning
confidence: 99%
“…However, several attempts towards polyploid induction in plants from the Cucurbitaceae family have been made. For instance, in Cucumis melo L., polyploids were successfully induced using oryzalin, where the obtained polyploid plants exhibited substantial morphological changes in seeds, leaves, and stomata compared with the diploid mother plants [18]. A similar study on the same species reported a higher total soluble solid content in tetraploid fruits than in diploid fruits [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutagen effects of colchicine and EMS are reported to effectively provide morphological variation and alter cell metabolism in Crocus sativus L (Samadi et al 2022). Application of colchicine to Cucumis melo "Chammel" resulted in tetraploid plants whose seeds were wider and heavier than their diploid (Woo et al 2021). Colchicine is also used as a mutagen in gladiolus, petunias, calendula, and chrysanthemums to increase the aesthetic value of such ornamental plants.…”
Section: Phenotypic Performances Of Srikayang Shallot M1mentioning
confidence: 99%